Understanding iPhone Purchase Decisions: The Effects of Product Quality, Brand Image, and Fear Of Missing Out (FOMO) with Consumer Trust as a Mediating Mechanism - Joy Verna Detta Br Regar; Rusdi Hidayat Nugroho (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of product quality, brand image, and Fear of Missing Out (FOMO) on iPhone purchasing decisions with consumer trust as an intervening variable among students of the Business Administration Study Program at UPN “Veteran” East Java. This research employed a quantitative approach using a survey method involving 150 iPhone users from the 2022–2024 cohorts selected through purposive sampling. The collected data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 through outer model evaluation, inner model evaluation, and bootstrapping hypothesis testing. The results indicate that product quality, brand image, and FOMO have positive and significant effects on consumer trust and purchasing decisions, with the strongest direct influence found in the relationship between brand image and consumer trust with a coefficient value of 0.426. Furthermore, consumer trust successfully mediates the effects of product quality, brand image, and FOMO on purchasing decisions, supporting previous studies that both functional and psychological factors influence smartphone purchasing behavior. This study concludes that improving product quality, strengthening brand image, and implementing digital trend-based marketing strategies can increase consumer trust and encourage iPhone purchasing decisions. Companies are advised to continuously maintain product quality, innovation, and security, while future researchers are encouraged to incorporate additional variables such as price, lifestyle, promotion, and electronic word of mouth with broader research coverage.